SUSTAINABLE DEVELOPMENT – CONDITION FOR THE SURVIVAL OF THE PLANET - BRAN, Florina; IOAN, Ildiko (Economics of Agriculture, 2018)
Societys desire for continued progress has found in the economic development the necessary support to foreshadow the future of human evolution. This attempt is another characteristic of people, to try to guess the direction, purpose and manage all of this at individual, community and nation level. This has created a range of possible options for an economic future, differentiated after the authors philosophy, simplifications made in the choice of variables etc. This shift of emphasis from man to nature was the result of limited intake of natural resources proving in the process of human evolution, continued growth of world population, extension of environmental pollution process. New limiting or pessimistic concepts of economic development appeared, which foreshadow the deep crisis that threatens civilization today. The mans complex thinking systems at the beginning of the third millennium should also outline the biunivocal nature-society dimension.